Perbandingan Kinerja Keuangan Perusahaan Sub Sektor Hotel, Restoran dan Pariwisata Yang Terdaftar Di Bursa Efek Indonesia Sebelum Dan Saat Pandemi Covid-19 - Rochmatul Fitriani; Titi Rapini; Riawan Riawan (Edumedia Solution, 2023)
This study aims to determine the performance of the hotel, restaurant, and tourism sub-sector companies listed on the Indonesia Stock Exchange and whether there were differences before and during the Covid-19 pandemic. To find out the company's performance, this research uses the profitability ratio, namely Return On Assets and Net Profit Margin, the liquidity ratio, namely the Current Ratio, and the activity ratio, namely working capital turnover. The population in this study are the hotel, restaurant, and tourism sub-sector companies listed on the Indonesia Stock Exchange in 2019 and 2020. Data were collected using quantitative data analysis by analyzing secondary data using a purposive sampling method. So we obtained 22 companies as a sample. The data analysis method used was paired sample t-test and Wilcoxon signed rank test, which previously carried out descriptive statistical tests and normality tests. The results of the data analysis show that there are significant differences in Return On Assets, Net Profit Margin, and working capital turnover, and there are no differences in the Current Ratio before and during the Covid-19 pandemic.